Об одном обобщении полиэдральной когерентной меры риска - Кирилюк, В.С. (Теорія оптимальних рішень, 2004)
A notion of the polyhedral measure, which generalizes the notion of the polyhedral coherent risk measure, is introduced. It allows within the framework of the uniform approach to study properties of wider class, which contains a number known risk measures (noncoherent as well). As shown, portfolio optimization problems for risk measures from this class are reduced to appropriate linear programming problems.